Postnatal growth velocity and overweight in early adolescents: A comparison of rural and urban African boys and girls. Issue 5 (20th June 2014) - Chirwa, E.D.; Griffiths, P.; Maleta, K.; Ashorn, P.; Pettifor, J.M.; Norris, S.A.
Abstract : Objectives: To compare growth velocity of two African child cohorts and examine the relationship between postnatal growth velocity in infancy/early childhood and the risk of overweight/stunting in early adolescence. Methods: The study used data from two child cohorts from urban (Birth to Twenty Cohort, South Africa) and rural (Lungwena Child Survival Study, Malawi) African settings. Mixed effect modelling was used to derive growth and peak growth velocities. T ‐tests were used to compare growth parameters and velocities between the two cohorts. Linear and logistic regression models were used to determine the relationship between growth velocity and early adolescent (ages 9–11 years) body mass index and odds of being overweight. Results: Children in the BH cohort were significantly taller and heavier than those in the Lungwena cohort, and exhibited faster weight and height growth velocity especially in the first year of life ( P  < 0.05). No significant association was shown between baseline weight ( α w ) and overweight in early adolescence (OR = 1.25, CI = 0.67, 2.34). The weight growth velocity parameter β w was highly associated with odds of being overweight. Association between overweight in adolescence and weight velocity was stronger in infancy than in early childhood (OR at 3 months = 4.80, CI = 2.49, 9.26; OR at 5 years = 2.39, CI = 1.65, 3.47). Conclusion: High weight and height growth velocity in infancy, independent of size at birth, is highly associated with overweight in early adolescence. However, the long term effects of rapid growth in infancy may be dependent on a particular population's socio‐economic status and level of urbanization. Am. J. Hum. Biol. 26:643–651, 2014. © 2014 The Authors American Journal of Human Biology Published by Wiley Periodicals, Inc.